Coronavirus enteritis progression in cattle with mineral deficiencies - Polkovnichenko Petr A.; Polkovnichenko Pavel A.; Larina Yulia V.; Kalyuzhnaya Maria P. (BIO Web of Conferences)
The article presents data on the shortage and content of trace elements in cattle, which leads to a wide range of pathologies, impaired reproduction, and a decrease in both dairy and meat productivity. The animal protection system, developed in the course of evolution to combat natural poisons, sources of man-made pollution and any animal disease, ultimately affects safety and productivity. The study of the development and prevention of the causes of these diseases, the effect of micronutrient deficiencies on the resistance of the animal body in the case of coronavirus infection, the development of treatment methods and preventive measures is an urgent problem today.